2023
DOI: 10.3389/fphys.2023.1288472
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a maternal and offspring obesogenic diet on daughter’s oocyte mitochondrial ultrastructure and bioenergetic responses. Insights from an outbred mouse model

Inne Xhonneux,
Waleed F. A. Marei,
Ben Meulders
et al.

Abstract: Obesity affects oocyte mitochondrial functions and reduces oocyte quality and fertility. Obesity may also increase the risk of metabolic disorders in the offspring. Children are likely to follow their parents lifestyle and diet, which also contributes to the increased prevelance of obesity across generations. We hypothesise that the impact of obesogenic (OB) diet and obesity on oocyte mitochondrial functions is different in offspring born to obese mothers compared to those born to healthy mothers. To test this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…Previous research has established that a maternal high-fat diet in outbred mice results in increased F1 oocyte MT ultrastructural abnormalities compared to control [38]. In our results, we showed that the percentage of abnormal mitochondria was slightly increased in HF/HS oocytes compared to CONT.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Previous research has established that a maternal high-fat diet in outbred mice results in increased F1 oocyte MT ultrastructural abnormalities compared to control [38]. In our results, we showed that the percentage of abnormal mitochondria was slightly increased in HF/HS oocytes compared to CONT.…”
Section: Discussionsupporting
confidence: 62%
“…In the F0 mice, the increase in MT ultrastructural abnormalities in HF/HS compared to CONT was 9%, and this was associated with decreased developmental competence of these oocytes after in vitro fertilization (IVF) [31]. Also, in another study, increased oocyte MT ultrastructural abnormalities were associated with alterations in MT membrane potential (MMP) and reactive oxygen species (ROS) accumulation in oocytes, as well as abnormal lipid droplet accumulation [38]. In contrast, here, in the offspring, the increase in MT ultrastructural abnormalities in HF/HS compared to CONT was only 3.2%.…”
Section: Discussionmentioning
confidence: 95%
“…All primordial, primary, and secondary follicles in each section were examined. To compare the oocyte mitochondrial morphology in preantral follicles with the already well described mitochondrial morphology of mature (ovulated) oocytes, few ovulated oocytes were collected of adult C»C offspring, according to the protocol described by Xhonneux [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, other specific ultrastructural features which clearly illustrate an abnormality or defect in the oocyte mitochondrial were classified separately, such as mitochondria showing loose inner membranes, broken or protruded outer membranes, rose-petal shaped mitochondria, enlarged mitochondria (>1μm), and mitochondria having electron dense foci. These forms were collectively classified here as abnormal mitochondria, as described in mature oocytes by Marei [ 20 ] and Xhonneux [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation